Practicing What We Preach: Investigating the Role of Social Support in Sport Psychologists’ Well-Being - McCormack, Hannah M.; MacIntyre, Tadhg E.; O’Shea, Deirdre; Campbell, Mark J.; Igou, Eric R. (Frontiers in Psychology, 2015)
Well-being and mental health of psychologists and their clients can be strongly linked to the psychologists’ experience of work. We know from general theories of occupational health psychology that certain work factors will have a greater impact on well-being than others. Work engagement is positively related with occupational health, while burnout and workaholic tendencies relate negatively. An individual’s resources can buffer against these negative effects. Specifically, the environmental resource of social support can impede the impact and instance of workaholism and has a positive influence on burnout. Social support is often encouraged by sport psychologists in protecting an athlete’s well-being. Drawing on theory and research from work and organisational, health and social psychology we explore the lived experiences of burnout and work engagement among applied sport psychologists, investigating their perceptions of how these experiences impact their well-being. Thirty participants from five countries were asked, using semi-structured interviews, to recall specific incidents when feelings of work engagement and burnout occurred. We examined the influence of social support and its impact on these incidents. Thematic analysis revealed that burnout is frequently experienced despite high levels of work engagement. Sources of social support differ between groups of high burnout versus low burnout, as does reference to the dimensions of work engagement. Avenues for future research including investigating the role of mindfulness and therapeutic lifestyle changes for practitioners are outlined.